Exploring students’ perception edu-tourism in Malaysia: an empirical study - Rahman, Mohammad Moshiur; Haque, A. K. M. Ahasanul; Shuib, Fatin Husna; Kabir, SMH (2019)
Edu-tourism and education encompass with globalization involving same history over the years. It has been identified that Malaysia has become prominent destination among students for affordable living cost and quality education. The purpose of this study was to investigate the potential of Edu-tourism business in Malaysia and students’ perception towards selection of a destination for education which fundamentally changes tourism dynamics and faces the challenges of redressing Edu-tourism. In this research, data were analyzed based on factor analysis and to test the suggested research hypotheses structural equation modeling using AMOS is applied. Data were collected through survey questionnaires from a total number of 228 students which were undergraduate and postgraduate students. However, this primary study was directed to realize the factors which create impact on students to select IIUM (International Islamic University Malaysia) as their foreign learning institute. Moreover, it has been found that “perceived value” mediate the relationship between students’ perception and students’ need towards selection of educational institute. Meanwhile, it ascertains guidelines for potential research in international educational tourism will influence students’ perception towards Edu-tourism and promote a general process of combination through comprehensive learning into touristic way.